INVESTIGATION OF THE LOSSES OF PHOTOVOLTAIC SOLAR SYSTEMS DURING OPERATION UNDER PARTIAL SHADING - Kuznetsov, Pavel Nikolaevich; Abd ali, Layth Mohammed; Kuvshinov, Vladimir Vladislavovich; Issa, Hayder Abdulsahib; Mohammed, Hayder Jasim; Al Barmani, Ali Ghanim (Journal of Applied Engineering Science, 2020)
:The article deals with research in solar power plants and Renewable Energy Laboratory. The purpose of research was to study the influencing of partial shading on the energy efficiency of photovoltaic installations in various switching options. As the title implies the article describes a study of the possibilities of increasing their energy efficiency when operating under different conditions. It is spoken in detail about replacement of "block switching" panels to the "in-line switching", in case of partial shading by the previous string. It is shown that substitution allows to obtain a significantly higher power - up to 8 times. It is examined that the horizontal arrangement of the panels instead of the vertical, under the same conditions, also allows up to 5 times the power of the partially shaded module in the case "in-line switching" and by 34% in the case of a "block switching". It is analyzed that parallel switching of partially shaded photovoltaic modules with normally illuminated, requires voltage matching, for the selection of electrical energy at the point of maximum power, which makes it possible to obtain much more energy from the shaded module. It is experimentally shown that when using the "Intelligent maximum power selection device" that implements the voltage matching, it is possible to increase the module power up to 4 times with partial shading of 3 panels of 18. It should be noted that the choice of methods that allow receiving energy from shaded panels through individual matching converters does not permit significantly increasing the energy production of partially shaded modules. It is experimentally shown that as a result of their use the module power does not increase by more than 2.5%. The results of research can be used in the design of new installations based on photovoltaic cells and the modernization of existing ones.